Serum amyloid A3 is pro-atherogenic. (January 2018) - Thompson, Joel C.; Wilson, Patricia G.; Shridas, Preetha; Ji, Ailing; de Beer, Maria; de Beer, Frederick C.; Webb, Nancy R.; Tannock, Lisa R.
Abstract: Background and aims: Serum amyloid A (SAA) predicts cardiovascular events. Overexpression of SAA increases atherosclerosis development; however, deficiency of two of the murine acute phase isoforms, SAA1.1 and SAA2.1, has no effect on atherosclerosis. SAA3 is a pseudogene in humans, but is an expressed acute phase isoform in mice. The goal of this study was to determine if SAA3 affects atherosclerosis in mice. Methods: ApoE -/- mice were used as the model for all studies. SAA3 was overexpressed by an adeno-associated virus or suppressed using an anti-sense oligonucleotide approach. Results: Over-expression of SAA3 led to a 4-fold increase in atherosclerosis lesion area compared to control mice ( p  = 0.01). Suppression of SAA3 decreased atherosclerosis in mice genetically deficient in SAA1.1 and SAA2.1 ( p  < 0.0001). Conclusions: SAA3 augments atherosclerosis in mice. Our results resolve a previous paradox in the literature and support extensive epidemiological data that SAA is pro-atherogenic. Highlights: Increased expression of SAA3 increases atherosclerosis development. Suppression of SAA3 in mice deficient in SAA1.1 and SAA2.1 attenuates atherosclerosis development. SAA3 has pro-atherogenic activity in mice.